2020
DOI: 10.3390/vaccines8040749
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Technology-Mediated HPV Vaccination Awareness Intervention: A Controlled, Quasi-Experimental, Mixed Methods Study

Abstract: College-aged women and men are an important catch-up population for human papillomavirus (HPV) vaccination interventions. Limited research has explored technology-mediated HPV vaccination awareness interventions aimed at college students. The purpose was to evaluate a novel, technology-mediated, social media-based intervention to promote HPV vaccination among college students. A controlled, quasi-experimental, mixed methods study examined the feasibility of a technology-based intervention among two undergradua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…Similarly, one feasibility study delivered an HPV vaccine intervention to undergraduate students via Facebook and electronic news. The intervention increased students' knowledge about HPV and the HPV vaccine but did not impact students' vaccine uptake [32]. To our knowledge, only one intervention study has reported the role of social media in influencing vaccine uptake behavior.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, one feasibility study delivered an HPV vaccine intervention to undergraduate students via Facebook and electronic news. The intervention increased students' knowledge about HPV and the HPV vaccine but did not impact students' vaccine uptake [32]. To our knowledge, only one intervention study has reported the role of social media in influencing vaccine uptake behavior.…”
Section: Discussionmentioning
confidence: 75%
“…A US RCT reported that education through social media is effective for improving general awareness regarding vaccination. However, the study was limited to a sample of 58 participants [ 22 ]. A phase 2 Japanese trial evaluated how the extent of intervention affected HPV vaccination acceptance and reported that providing appropriate medical information resulted in beneficial effects [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study proved the utility of effective and adequate guidance in improving vaccine acceptance. There is a paucity of literature on the efficacy of pragmatic educational materials for HPV vaccination promotion [ 22 ]. Therefore, more extensive trials focusing on the mode of endorsing HPV vaccination like our trial are required for evidence-based promotion.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Appendix B , three domains accounted for the overall judgment: relevancy, reliability, and validity. The included studies were scored medium and high in total score (13 articles were rated between 7 and 9 [ 25–37 ], seven studies were between 4 and 6 [ 38–44 ]). Then the overall score for each domain was counted.…”
Section: Methodsmentioning
confidence: 99%
“…The validity domain presented the lowest score due to the potential methodological bias. Among these, the issue of small sample size was the most frequent issue which has been found in six studies [ 25 , 26 , 28 , 36 , 38 , 44 ], followed by the lack of generalization in six studies [ 25 , 28 , 33 , 37 , 38 , 40 ], and response bias caused by self-reported measures in three studies [ 26 , 35 , 39 ]. Three studies also reported the inability to measure the outcome due to the study design that leads to the difficulty in distinguishing the impact factors [ 33 , 35 , 40 ].…”
Section: Methodsmentioning
confidence: 99%